2017
DOI: 10.1097/md.0000000000007774
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative characteristics of infants who developed necrotizing enterocolitis with different postnatal ages

Abstract: Our goal was to investigate the surgical procedures, postoperative complications, and survival with regard to different onset timing of necrotizing enterocolitis (NEC).We performed a retrospective review of medical records with a diagnosis of NEC between 2005 and 2016. The cutoff was set at 10 days for early onset ≤10 days and late onset over 10 days. Propensity score matching was performed to adjust for any baseline differences. In 53 paired patients, clinical outcomes, including, mortality, postoperative com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…Lower birth weight and SGA/IUGR has been proved to be associated with delayed total enteral feeding in many studies [9,20,23].The inferior feeding tolerance and outcomes in them were probably due to the redistribution of blood ow in fetal and the persist abnormalities of gastrointestinal blood ow postnatal [28,29].Those smaller infants with a higher proportion of SGA,was supposed to have a longer duration of time to achieving total enteral feeding.However,in our study, no statistical difference was found between groups at the time of achieving total enteral feeding or FI.That is inconsistent with the studies of Xiang Y, et al [30]. and Hu F, et al [31].We speculated the reason is probably the subject of our study were mainly late preterm infants,who has a relatively better tolerance of enteral feeding, diminishing the effect of lower birth weight on enteral feeding,in addition, those factors that might affect enteral feeding were not signi cantly different between groups [32][33][34][35][36][37].…”
Section: Discussioncontrasting
confidence: 90%
“…Lower birth weight and SGA/IUGR has been proved to be associated with delayed total enteral feeding in many studies [9,20,23].The inferior feeding tolerance and outcomes in them were probably due to the redistribution of blood ow in fetal and the persist abnormalities of gastrointestinal blood ow postnatal [28,29].Those smaller infants with a higher proportion of SGA,was supposed to have a longer duration of time to achieving total enteral feeding.However,in our study, no statistical difference was found between groups at the time of achieving total enteral feeding or FI.That is inconsistent with the studies of Xiang Y, et al [30]. and Hu F, et al [31].We speculated the reason is probably the subject of our study were mainly late preterm infants,who has a relatively better tolerance of enteral feeding, diminishing the effect of lower birth weight on enteral feeding,in addition, those factors that might affect enteral feeding were not signi cantly different between groups [32][33][34][35][36][37].…”
Section: Discussioncontrasting
confidence: 90%
“…Our findings are similar to several past studies ( 19 25 ). Li et al ( 21 ) noted that infants with earlier onset of NEC had achieved full feedings earlier (means ± standard deviation 18.1±11.5 vs . 26.3±15.6 days, p =0.008), had less mortality ( p =0.026), and showed a trend for fewer infections [19/53 (35.8%) vs .…”
Section: Discussionmentioning
confidence: 99%
“…When the disease was limited, the outcome seemed more favorable. [ 20 , 21 ] The lower survival was observed for infants with pan-intestinal involvement compared with limited disease of NEC. [ 22 , 23 ] In the present study, when the rectum, jejunum, and ileum were involved for the disease, which means greater extent, there were more patients who died.…”
Section: Discussionmentioning
confidence: 99%